2019
DOI: 10.1155/2019/2971741
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response and Virulence Potential Modulating Effect of Peppermint Essential Oil inCampylobacter jejuni

Abstract: Campylobacter jejuni is one of the most common food-borne bacteria that causes gastrointestinal symptoms. In the present study we have investigated the molecular basis of the anti-Campylobacter effect of peppermint essential oil (PEO), one of the oldest EO used to treat gastrointestinal diseases. Transcriptomic, quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and proteomic, two-dimensional polyacryl amid gel electrophoresis (2D-PAGE) methods have revealed that, in the presence of a suble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Others report impaired motility and adhesion of C. jejuni by clove oil, thyme and the so-called campynexins (Johnson et al 2015), and modulation of stress response and virulence effects of C. jejuni by peppermint essential oil (Kovács et al 2019). Castillo et al (2011) showed that extracts of Acacia farnesiana (sweet acacia) and Artemisia ludoviciana (silvery mugwort) inhibited CDT production in C. jejuni and C. coli (Castillo et al 2011).…”
Section: Natural Products and Plant Extracts Against Campylobactermentioning
confidence: 99%
“…Others report impaired motility and adhesion of C. jejuni by clove oil, thyme and the so-called campynexins (Johnson et al 2015), and modulation of stress response and virulence effects of C. jejuni by peppermint essential oil (Kovács et al 2019). Castillo et al (2011) showed that extracts of Acacia farnesiana (sweet acacia) and Artemisia ludoviciana (silvery mugwort) inhibited CDT production in C. jejuni and C. coli (Castillo et al 2011).…”
Section: Natural Products and Plant Extracts Against Campylobactermentioning
confidence: 99%
“…The VBNC form of Campylobacter has been categorized based on reduced metabolism, augmented production of the degrading enzymes and substrates, and ( Chaveerach et al, 2003 ; Upadhyay et al, 2019 ). Consequently, microbes can live for longer periods in hostile conditions ( Kovacs et al, 2019 ).…”
Section: Viable But Non-culturable (Vbnc) Statementioning
confidence: 99%
“…They displayed acidic cross-protection, which initiated ATR under oxygen or air status. In addition, the ATR initiation of microbes at pH 4.5 varies according to the culture media; this might be due to the different nutrient compositions of the various culture media ( Kovacs et al, 2019 ), -. C .…”
Section: Adaptation To Major Environmental Stresses By Campmentioning
confidence: 99%
See 2 more Smart Citations